PAn/Cu Bismuthate Nanoflake Composites with Enhanced Electrochemical Performance for TA - Wang, Z.; Chen, H.J.; Lin, F.F.; Yan, L.; Zhang, Y.; Pei, L.Z.; Fan, C.G. (Micro and Nanosystems, 2020)
Background: Measuring tartaric acid in liquid food, such as fruits or fruit products is of great importance for assessing the quality of the food. Objective: The aim of the research is to obtain polyaniline/Cu bismuthate nanoflake composites by an in-situ polymerization route for the electrochemical detection of tartaric acid. Methods: Polyaniline/Cu bismuthate nanoflake composites were prepared by in-situ aniline polymerizing route in aqueous solution. The obtained products were characterized by X-Ray diffraction (XRD), Transmission Electron Microscopy (TEM) and high-resolution TEM (HRTEM), respectively. The electrochemical performance for tartaric acid detection has been investigated by cyclic voltammetry method using polyaniline/Cu bismuthate nanoflake composites modified glassy carbon electrode. Results: The nanocomposites comprise of tetragonal CuBi2O4 phase. Polyaniline particles with the size of less than 100 nm attach to the surface of the nanoflakes. A pair of quasi-reversible cyclic voltammetry peaks are located at -0.01 V and +0.04 V, respectively at the 20wt.% polyaniline/Cu bismuthate nanoflake composites modified glassy carbon electrode. The limit of detection is 0.58 μM with the linear range of 0.001-2 mM. The linear range increases from 0.005-2 mM to 0.001-2 mM and limit of detection decreases from 2.3 μM to 0.43 μM with increasing the polyaniline content from 10wt.% to 40wt.%. Conclusion: Comparing with the Cu bismuthate nanoflakes modified glassy carbon electrode, polyaniline/ Cu bismuthate nanoflake composites modified glassy carbon electrode shows enhanced electrochemical performance for tartaric acid detection.
Keywords: Cu bismuthate nanoflakes